2019
DOI: 10.1038/s41467-019-13577-5
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of human myeloid-derived growth factor suggests a conserved function in the endoplasmic reticulum

Abstract: Human myeloid-derived growth factor (hMYDGF) is a 142-residue protein with a C-terminal endoplasmic reticulum (ER) retention sequence (ERS). Extracellular MYDGF mediates cardiac repair in mice after anoxic injury. Although homologs of hMYDGF are found in eukaryotes as distant as protozoans, its structure and function are unknown. Here we present the NMR solution structure of hMYDGF, which consists of a short α-helix and ten β-strands distributed in three β-sheets. Conserved residues map to the unstructured ERS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…C19orf10 is highly conserved in evolution and is mainly localized in the Golgi and endoplasmic reticulum, but it functions extracellularly [8]. The N-terminus and C-terminus of human C19orf10 contain a signal peptide and a conserved sequence of the endoplasmic reticulum, respectively, but human C19orf10 has no sequence homology with any other proteins [9]. Structural analysis has revealed that C19orf10 consists of 10 antiparallel β-strands forming a β-sandwich, and its folding topology is not similar to other cytokines or growth factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…C19orf10 is highly conserved in evolution and is mainly localized in the Golgi and endoplasmic reticulum, but it functions extracellularly [8]. The N-terminus and C-terminus of human C19orf10 contain a signal peptide and a conserved sequence of the endoplasmic reticulum, respectively, but human C19orf10 has no sequence homology with any other proteins [9]. Structural analysis has revealed that C19orf10 consists of 10 antiparallel β-strands forming a β-sandwich, and its folding topology is not similar to other cytokines or growth factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here we use MYDGF (Myeloid Derived Growth Factor) as an example KO gene to illustrate this application of scTenifoldKnk. MYDGF , also known as C19orf10 , is a 142-residue protein broadly expressed in multiple tissues and cell types [79, 80]. Mydgf has been shown in a mouse model to enhance cardiac myocyte survival, tissue repair, and angiogenesis caused by myocardial infarction [81].…”
Section: Resultsmentioning
confidence: 99%
“…MYDGF , also known as C19orf10 , is a 142-residue protein broadly expressed in multiple tissues and cell types. 58,59 Mydgf has been shown in a mouse model to enhance cardiac myocyte survival, tissue repair, and angiogenesis caused by myocardial infarction. 60 To elucidate MYDGF ’s function, we downloaded multiple human scRNAseq data sets from the PanglaoDB database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This physiological event leads to an alteration in metabolic machinery accompanied by predominance of glycolysis and protection from damage by free radicals (20). This cellular stress is the main trigger for secretion of myeloid-derived growth factor (MYDGF) protein to act as a paracrine/autocrine survival factor, a notion that justi es upregulation of this protein in FT (21). It is the rst report of differential expression of MYDGF protein in FT and TP.…”
Section: Discussionmentioning
confidence: 99%